Analysis of The Effect of Aluminum Electrode Geometry on The Removal of Polyethylene Microbeads Using The Electrocoagulation Method in Greywater - Ferdy Ashari Syawal; Zulkarnaini Zulkarnaini; Shinta Indah; Fadhila Fadhila (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Abstract: The increasing use of cosmetics and personal care products containing small-sized and low-density microbeads will disrupt the aquatic environment because they are difficult to remove in wastewater treatment plants (WWTPs). Electrocoagulation (EC) is an effective technology for removing microbeads from greywater. This research aims to develop an effective cylindrical electrode geometry design in the EC process to reduce electrode passivation, as evidenced by the removal of polyethylene (PE) microbeads from greywater, reduced energy consumption, and the analysis of the EC kinetics model. Experiments were carried out on batch and continuous systems using artificial greywater with an initial concentration of 0.5 g/L. Variations made in the batch system are the geometry of the cylindrical electrode without holes (ESTB), a cylindrical electrode with holes (ESB), a cylindrical electrode with anode with holes, and a cathode with no holes (ESB-A), a cylindrical electrode with cathode, with holes and anode with no holes (ESB-K), and plate electrode (EP). The variations carried out in the continuous system were flow rates of 60, 70, 80, and 90 mL/minute using the best electrode geometry design obtained from the batch system. The best removal efficiency of PE microbeads in a batch system was 98.44% in ESB-K geometry and saved 75% energy consumption compared to EP. The best removal efficiency of PE microbeads in a continuous system was 79.76% at a flow rate of 60 mL/minute. The kinetic model of the EC reaction which corresponds to the removal process of PE microbeads is a first-order reaction. Future research should focus on optimizing the design of continuous reactors so that they can be applied to tertiary processing in domestic WWTPs and industrial WWTPs.Abstrak: Meningkatnya penggunaan kosmetik dan produk perawatan pribadi (CPCP) yang mengandung microbeads berukuran kecil dan berkepadatan rendah akan mengganggu lingkungan perairan karena sulit disisihkan di instalasi pengolahan air limbah (IPAL). Elektrokoagulasi adalah teknologi yang efektif untuk menyisihkan microbeads dari greywater. Penelitian ini bertujuan untuk mengembangkan desain geometri elektroda silinder yang efektif pada proses elektrokoagulasi untuk mengurangi pasivasi elektroda yang dibuktikan dari penyisihan microbeads polyethylene dari greywater dan pengurangan konsumsi energi yang digunakan dan menganalisis model kinetika elektrokoagukasi. Eksperimen dilakukan pada sistem batch dan kontinu menggunakan greywater artifisial dengan konsentrasi awal 0,5 g/L. Variasi yang dilakukan pada sistem batch adalah geometri elektroda silinder tidak berlubang (ESTB), elektroda silinder berlubang (ESB), elektroda silinder anoda berlubang dan katoda tidak berlubang (ESB-A), elektroda silinder katoda berlubang dan anoda tidak berlubang (ESB-K), dan elektroda pelat (EP). Variasi yang dilakukan pada sistem kontinu adalah laju alir 60, 70, 80, dan 90 mL/menit menggunakan desain geometri elektroda terbaik yang diperoleh dari sistem batch. Efisiensi penyisihan microbeads polyethylene terbaik pada sistem batch sebesar 98,44% pada geometri ESB-K dan menghemat 75% konsumsi energi dibandingkan EP. Efisiensi penyisihan microbeads polyethylene terbaik pada sistem kontinu sebesar 79,76% pada laju alir 60 mL/menit. Model kinetika reaksi elektrokoagulasi yang sesuai dengan proses penyisihan microbeads polyethylene adalah reaksi orde satu. Penelitian selanjutnya harus berfokus pada optimalisasi desain reaktor kontinu, sehingga dapat diterapkan pada pengolahan tersier di IPAL domestik maupun IPAL industri.